URBAN FLOOD VULNERABILITY MAPPING OF LAGOS, NIGERIA - Kaoje, Ismail Usman; Ishiaku, Ibrahim (MATTER: International Journal of Science and Technology, 2017)
The paper aimed to demonstrate how the application of HEC-RAS and GIS techniques can be utilized for better results when carrying out a flood vulnerability mapping and assessment. Digital interpretation that uses HEC-RAS and GIS to conduct hydraulic modelling, flood inundation mapping and visualization were adapted. Similarly, Digital Terrain Model (DTM) and aerial imagery of lansat8 OLI of the study area were used. The data were analysed with the aid of ArcGIS 10.1 application with HEC-GeoRAS tool extension and HEC-RAS 4.1 software application. The results showed: 1) the flood vulnerability map of Lagos (Figure 4) generated using the combination GIS techniques and RAS packages. The flood risk depicted shown areas that have 1 % probability of flood occurrence in 100 years; 2) The topography of Lagos (Figure 5) indicated the pattern of the city terrain to be relatively flat in the centre and it also has few meters high above sea level especially in the south-eastern areas; 3) of the 20 local government areas Lagos state (Figure 6) only two (Agege and Ifako) were found not to be at risk of flooding. We concluded that flood vulnerability of this kind is important for Nigeria and other countries to aid decision on flood disaster planning.